Anti-cancer and anti-oxidant properties of ethanolic leaf extract of Thymus vulgaris and its bio-functionalized silver nanoparticles - Heidari, Zahra (3 Biotech, 2018)
This study highlights the anti-oxidant and anti-cancer activities of bio-functionalized Thymus vulgaris silver nanoparticles (TVAgNPs) and bioactive compounds were compared using the human breast cancer T47D cell line. The aqueous ethanolic extract of T. vulgaris evaluated for chemical composition using the gas chromatography–mass spectrometer (GC–MS) analysis. The prepared TVAgNPs were determined by means of UV–Vis spectroscopy, FTIR spectroscopy, zeta potential, scanning electron microscopy, transmission electron microscopy, and energy-dispersed spectroscopy analysis. The T. vulgaris extract and TVAgNPs were studied for their in vitro anti-oxidant property by 2, 2-diphenyl, 1-picryl hydrazyl (DPPH) assay. Microscopic observations indicated spherical shaped and monodispersed nanoparticles and the average size of the nanoparticles was about 30 nm. Regarding the elemental composition profile of the TVAgNPs, the highest signal of silver (89.30%) was detected followed by other elements. An absorption peak was registered at 440 nm according to surface plasmon resonance (SPR) of the TVAgNPs in solution. A zeta potential of fabricated nanoparticles was approximately − 12.6 mV, indicating higher stability of the bio-functionalized TVAgNPs. The T. vulgaris extract and synthesized TVAgNPs were evaluated for their anti-cancer activity using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) assay and Annexin V double staining with propidium iodide (PI) flow cytometric analysis toward T47D cells. The cytotoxicity properties of the bio-functionalized T. vulgaris AgNPs revealed that the sensitivity of T47D human breast cancer cells is high compared with T. vulgaris extract. The Annexin V/PI staining indicated that the fabricated TVAgNPs shows increased apoptosis in T47D cells as compared to untreated cells. Besides, the anti-oxidant activity of the TVAgNPs clarified a higher anti-radical-scavenging activity compared to Thymus vulgaris extract. Our data show that the potential biological activities of the bioactive constituents of T. vulgaris can be enhanced through bio-functionalized T. vulgaris AgNPs due to the bioorganic compounds that exist in the extract.